The IMF's Data Dissemination Initiative After Ten Years - Alexander, William (International Monetary Fund, 2008)
The Data Dissemination Initiative was launched in the mid-1990s as part of a broader internationally-agreed-upon initiative to strengthen transparency and promote good governance practices by establishing standards and codes. Ten years later, the initiative is viewed as an integral part of the international financial architecture, and is considered to have improved the functioning of international financial markets and contributed to global financial stability. This volume reviews certain aspects of the development of and experience with the initiative over the past decade, and concludes by reflecting on potential challenges ahead and possible enhancements.